2015
DOI: 10.1002/pola.27758
|View full text |Cite
|
Sign up to set email alerts
|

New approach for producing fluorescent gold nanoparticles: Poly(ethylene oxide) homopolymers as reductants in the micelles of amphiphilic fluorosilicone-containing block copolymers

Abstract: INTRODUCTION Gold nanoparticles (AuNPs) or gold Nanoclusters (AuNCs) present special quantum size effect and exhibit fascinating size-related electronic, magnetic, optical, or fluorescent properties, which have extensive applications to catalysis, biology, and nanotechnology.1,2 In the past decade,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Encapsulation of AuNCs into polymer micelles has been previously reported using poly­(ethylene glycol)- b -poly­(ε-caprolactone) (PEG- b -PCL) and poly­(ethylene glycol)- b -poly­( N -isopropylacrylamide) (PEG- b -PNIPAM). , These works showed that polymer micelles lead to biocompatible hybrid nanomaterials with enhanced optical properties. , Moreover, the micelles were shown to protect the AuNCs from external agents, such as enzymes in a biological environment while controlling their interactions with the media, improving the control over their properties (avoiding changes in optical and electronic properties upon variation in pH or ionic strength of the media). , …”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation of AuNCs into polymer micelles has been previously reported using poly­(ethylene glycol)- b -poly­(ε-caprolactone) (PEG- b -PCL) and poly­(ethylene glycol)- b -poly­( N -isopropylacrylamide) (PEG- b -PNIPAM). , These works showed that polymer micelles lead to biocompatible hybrid nanomaterials with enhanced optical properties. , Moreover, the micelles were shown to protect the AuNCs from external agents, such as enzymes in a biological environment while controlling their interactions with the media, improving the control over their properties (avoiding changes in optical and electronic properties upon variation in pH or ionic strength of the media). , …”
Section: Introductionmentioning
confidence: 99%